The Role of Performance Management in Improving Employee Service Quality: A Literature Review Study - Ahmad Zayroni; Mochammad Isa Anshori (SAJMR : Southeast Asian Journal of Management and Research, 2024)
In an increasingly competitive era of globalization, performance management has become an essential element in efforts to improve the quality of organizational services. Performance management is a systematic process designed to increase organizational effectiveness through improving individual and team performance. This research uses qualitative research methods with literature study or literature review methods. The goal is to compare the hypothesis with existing theories in the scientific literature. The material used is literature from community service research that has been published in scientific journals at both national and international levels that are relevant to the research topic. This research reveals that performance management has a crucial role in improving service quality in various sectors. Through the implementation of an effective performance management system, significant improvements in employee productivity were found. In particular, this strategy has proven successful in optimizing individual and team performance, as well as improving the quality of services provided to consumers or the public.